2014
DOI: 10.1158/1078-0432.ccr-14-0363
|View full text |Cite
|
Sign up to set email alerts
|

To “Grow” or “Go”: TMEM16A Expression as a Switch between Tumor Growth and Metastasis in SCCHN

Abstract: Purpose Tumor metastasis is the leading cause of death in cancer patients. However, the mechanisms that underlie metastatic progression remain unclear. We examined TMEM16A (ANO1) expression as a key factor shifting tumors between growth and metastasis. Experimental Design We evaluated 26 pairs of primary and metastatic lymph node tissue from patients with squamous cell carcinoma of the head and neck (SCCHN) for differential expression of TMEM16A. Additionally, we identified mechanisms by which TMEM16A expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 27 publications
4
94
1
3
Order By: Relevance
“…A pro-proliferative role of ANO1 is found in most cancer cells investigated 118,[141][142][143][144][145][146] and Stanich and coworkers demonstrated that ANO1 regulates cell proliferation at the G1/S transition in the cell cycle. 147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g.…”
Section: Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…A pro-proliferative role of ANO1 is found in most cancer cells investigated 118,[141][142][143][144][145][146] and Stanich and coworkers demonstrated that ANO1 regulates cell proliferation at the G1/S transition in the cell cycle. 147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g.…”
Section: Proliferationmentioning
confidence: 99%
“…139 In contrast, Shiwarshi and coworkers find that reduced ANO1 expression slows proliferation and allow metastatic progression and they suggest that ANO1 expression is a switch between growth and metastasis. 143 …”
Section: Migration and Metastasismentioning
confidence: 99%
“…(Britschgi et al, 2013;Bill et al, 2015), but may also directly engage with MAP kinase pathways to promote growth and survival (Duvvuri et al, 2012;Sui et al, 2014). Although it is often reported in association with metastasis and recurrence in translational studies, other studies have reported effects on proliferation and local invasion (Ruiz et al, 2012;Shiwarski et al, 2014;Jia et al, 2015), suggesting the tumourigenic functions of Ano1 may be more complex than a 'grow to go' switch.…”
Section: Genes Chromosomes and Cancermentioning
confidence: 99%
“…As would be predicted based on these results, reduced levels of CFTR are associated with poor prognosis in breast cancer patients (Zhang et al 2013a). More recent studies have begun to explore chloride channels in the context of EMT in other cancer types, such as squamous cell carcinomas of the head and neck (Shiwarski et al 2014). TMEM16A (also known as ANO1), is one of a reported subset (termed Anoctamins) of calcium activated chloride channels (Kunzelmann et al 2011).…”
Section: Chloride Channels and Emt In Cancer Cellsmentioning
confidence: 94%
“…MCF-7). Indeed, expression of the EMT Shiwarski et al (2014) transcription factor Snail supresses CLCA2 protein in the human breast cell line MCF10A, and CLCA2 levels are reduced in subpopulations of cells from the human mammary epithelial (HMLE) cell line that are enriched in mesenchymal markers (Walia et al 2012). Moreover, CLCA2 levels are reduced during EMT induced by TGFβ (Yu et al 2013).…”
Section: Chloride Channels and Emt In Cancer Cellsmentioning
confidence: 99%